1,000 facts about insects - Honovich, Nancy; Lamp, Bill; National Geographic Society (U.S.) (Washington, D.C. : National Geographic, 2018)
"Information about insects formatted for children."--
10 fast facts -- Habitats -- Number crunching -- Ants -- Senses -- Aquatic insects -- Motion -- Fictional insects -- Disguises -- Life cycles -- Predators -- Foraging -- Architects -- At the extremes -- Genes -- Stingers, biters, and bloodsuckers -- Defenses -- Bees -- Forgotten insects -- Cousins -- Families -- Helpers -- Migration -- Fads -- Love bugs -- Machines -- Appetizing insects -- Societies -- Commemorative facts -- Communication -- Blood and guts -- Body snatchers -- Invasions -- Insect-eaters -- Lightmakers -- Butterflies -- Weird insects -- Endangered insects -- Beetles -- Conservation.
OSLIS\Gale Nat Geo eBooks(2/2/23).
Ages 8-12.
Grades 4 to 6.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Insects -- Miscellanea -- Juvenile literature; Children's questions and answers; Children's questions and answers; Insects -- Miscellanea; Questions and answers; JUVENILE NONFICTION -- Animals -- Insects, Spiders, etc; JUVENILE NONFICTION -- Reference; JUVENILE NONFICTION -- Science & Nature -- Zoology; Insects -- Miscellanea; Children's questions and answers; Children's nonfiction; Children's questions and answers; Insects; Electronic books- OSLIS; Children's nonfiction; Trivia and miscellanea; Juvenile works; Literature; Trivia and miscellanea; Literature; Electronic books